Pengaruh Online Customer Review, E-Wom, dan Kepercayaan Terhadap Minat Beli Cetaphil Gentle Skin Cleanser di Kota Batam - Michael Ovin; Suhardi Suhardi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
In the current digital era, the internet has become one of the main platforms for marketing and commerce. E-commerce makes it easier for consumers to shop online through easy access and price comparison features. This study aims to determine the effect of Online Customer Reviews (X1), electronic word of mouth (e-WOM) (X2), and trust (X3) on purchase intention toward the skincare product Cetaphil Gentle Skin Cleanser in Batam City. The approach used is quantitative research. Data were collected through the distribution of online questionnaires to 204 respondents who have used and purchased the product. The sampling technique employed was purposive sampling. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 29. The results show that Online Customer Reviews, e-WOM, and trust simultaneously have an effect on purchase intention. The magnitude of the influence of these three variables reaches 39.2%. Meanwhile, 60.8% of purchase intention is influenced by other factors outside the scope of this study. These findings indicate that Online Customer Reviews, e-WOM, and trust play an important role in shaping consumers’ purchase intention.